Assessing biogeochemical and human-induced drivers of soil organic carbon to inform restoration activities in Rwanda - Winowiecki, Leigh Ann; Mukuralinda, Athanase; Bargués Tobella, A.; Mujawamaria, P.; Ntawuhiganayo, E.B.; Mugayi, A.; Chomba, S.; Vågen, Tor-Gunnar (Copernicus GmbH, 2020)
Land restoration is of critical importance in Rwanda, where land degradation negatively impacts crop productivity, water, food and nutrition security. We implemented the Land Degradation Surveillance Framework in Kayonza and Nyagatare districts in eastern Rwanda to assess baseline status of key soil and land health indicators, including soil organic carbon (SOC) and soil erosion prevalence. We collected 300 topsoil (0–20 cm) and 281 subsoil (20–50 cm) samples from two 100 km2 sites. We coupled the soil health indicators with vegetation structure, tree density and tree diversity assessments. Mean topsoil organic carbon was low overall, 20.9 g kg−1 in Kayonza and 17.3 g kg−1 in Nyagatare. Stable carbon isotope values (d13CV-PDB ) ranged from −15.35 to −21.34 ‰ indicating a wide range of plant communities with both C3 and C4 photosynthetic pathways. Soil carbon content decreased with increasing sand content across both sites and at both sampling depths and was lowest in croplands compared to shrubland, woodland and grasslands. Field-saturated hydraulic conductivity (Kfs) was estimated based on infiltration measurements, with a median of 76 mm h−1 in Kayonza and 62 mm h−1 in Nyagatare, respectively. Topsoil OC had a positive effect on Kfs, whereas pH, sand and compaction had negative effects. Soil erosion was highest in plots classified as woodland and shrubland. Maps of soil erosion and SOC at 30-m resolution were produced with high accuracy and showed high variability across the region. These data and analysis demonstrate the importance of systematically monitoring multiple indicators at multiple spatial scales to assess drivers of degradation and their impact on soil organic carbon dynamics.